2006
DOI: 10.1111/j.1529-8817.2006.00236.x
|View full text |Cite
|
Sign up to set email alerts
|

A SYNECHOCOCCUS PCC7942 ΔCCMM (CYANOPHYCEAE) MUTANT PSEUDOREVERTS TO AIR GROWTH WITHOUT REGAINING CARBOXYSOMES1

Abstract: In the cyanobacteria, intracellular structures called carboxysomes function to concentrate CO 2 around the relatively inefficient CO 2 -fixing enzyme RUBISCO. Mutants devoid of carboxysomes, such as the Synechococcus PCC7942 DccmM mutant, are able to grow at high-CO 2 (2% v/v CO 2 in air) but perish in air. By growing DccmM in air containing 0.23% CO 2 , and then normal air (0.037%) it was possible to isolate spontaneous pseudorevertant colonies (PsrDccmM) that still lack ccmM and carboxysomes but can grow in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…This may be particularly essential for those cells that do not produce small carboxysome-like structures. Of note, a previous study reported that a carboxysome-less pseudorevertant Δ ccmM Syn7942 mutant could survive in air ( 40 ). Further investigations are needed to tackle this question.…”
Section: Discussionmentioning
confidence: 99%
“…This may be particularly essential for those cells that do not produce small carboxysome-like structures. Of note, a previous study reported that a carboxysome-less pseudorevertant Δ ccmM Syn7942 mutant could survive in air ( 40 ). Further investigations are needed to tackle this question.…”
Section: Discussionmentioning
confidence: 99%
“…Under high CO 2 concentration (1% v/v), the Δ ccmKLMN mutant maintains flux ratios in central pathways similar to the control strain. In previous reports, quantitative RT-PCR and microarrays were used to monitor the abundance of gene transcripts in both ΔccmM and wild type cyanobacterial cells grown in high CO 2 conditions (Emlyn-Jones et al, 2006; Hackenberg et al, 2012). Despite large transcriptional changes seen in genes involved in photosynthesis, high-light stress, and N assimilation in the Δ ccmKLMN mutant, little-to-no transcriptional change was detected in its carbon uptake (i.e., genes encoding carbon transporter systems and transcriptional regulators), the Calvin Cycle, and other central metabolic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Other widely studied cyanobacterial strains grow significantly slower; for example, Synechocystis sp. PCC 6803 which was reported to have a doubling time of 12 h at (Vermass et al, 1988 ), and Synechococcus elongatus PCC 7942 with a doubling time of 6–7 h (Mori et al, 1996 ; Emlyn-Jones et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%